2016
DOI: 10.3934/molsci.2016.1.88
|View full text |Cite
|
Sign up to set email alerts
|

Triclosan antimicrobial polymers

Abstract: Triclosan antimicrobial molecular fluctuating energies of nonbonding electron pairs for the oxygen atom by ether bond rotations are reviewed with conformational computational chemistry analyses. Subsequent understanding of triclosan alternating ether bond rotations is able to help explain several material properties in Polymer Science. Unique bond rotation entanglements between triclosan and the polymer chains increase both the mechanical properties of polymer toughness and strength that are enhanced even bett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 40 publications
0
35
0
Order By: Relevance
“…Over the past few decades, researchers have designed and obtained approval for antibiotic-coated urinary catheters for use in clinical settings. However, due to the higher cost and contradictory results from in vitro studies and in clinical trials, their efficacy is brought into question [4,25,63,74,77,79,91,[102][103][104][105][106][107][108][109][110][111][112][113]. The most common antibiotics used include nitrofurazone, gentamicin, fluoroquinolones (norfloxacin, ciprofloxacin, sparfloxacin), triclosan, and chlorhexidine.…”
Section: Antibioticsmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the past few decades, researchers have designed and obtained approval for antibiotic-coated urinary catheters for use in clinical settings. However, due to the higher cost and contradictory results from in vitro studies and in clinical trials, their efficacy is brought into question [4,25,63,74,77,79,91,[102][103][104][105][106][107][108][109][110][111][112][113]. The most common antibiotics used include nitrofurazone, gentamicin, fluoroquinolones (norfloxacin, ciprofloxacin, sparfloxacin), triclosan, and chlorhexidine.…”
Section: Antibioticsmentioning
confidence: 99%
“…Triclosan has been used as an antiseptic for decades and it is commonly found in household products such as toothpaste and soaps [122]. Recently, triclosan has been proposed as a candidate for coating medical devices, since it chemical properties make it easy to coat the catheter material [113]. Although much research has shown the antimicrobial activity in vitro, its effects on the human body have not been fully studied.…”
Section: Triclosanmentioning
confidence: 99%
See 1 more Smart Citation
“…At lower concentrations, it is bacteriostatic by inhibiting an enzyme involved in fatty acid synthesis and, at higher concentrations, it is bacteric i d a l b y d e s t a b i l i z i n g m i c r o b i a l m e m b r a n e s . Compatibilization of triclosan with polymers may extend the duration of its wide-spectrum antimicrobial activity [123] and could prove effective in reducing environmental surface load of pathogens. Bacteriophages applied to surfaces and targeting specific microorganisms have been attempted and mixtures of phages have been further suggested in order to effectively reduce the environmental bioburden.…”
Section: Environmental Surfacesmentioning
confidence: 99%
“…Bacterial membrane phospholipids are disrupted by rapid triclosan fluctuating bond rotations. Although triclosan has been used for years its antimicrobial property, there is no data about bacterial resistance in humans [106].…”
Section: Mesh Modificationsmentioning
confidence: 99%